STRATEGI PENGELOLAAN COWORKING SPACE UNTUK MENGHADAPI PERSAINGAN BISNIS (OBJEK STUDI: CONCLAVE WIJAYA, KELURAHAN PETOGONGAN. KECAMATAN KEBAYORAN BARU, JAKARTA SELATAN) - Sinta Setiani; Suryono Herlambang; Liong Ju Tjung (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2020)
Conclave Wijaya has been established since 2013 and was inaugurated in 2014, Conclave Wijaya is not only focused on one type of function space but in addition to coworking space there is also built office space, meeting rooms, event spaces, auditoriums and class rooms. The identification of problems stems from the rapid development of startups and micro and small businesses, especially in Jakarta. But often times there are many new breakthroughs about the concept and function of coworking space that suits consumers' needs and of course at affordable prices. Although Conclave Wijaya cooperates with Comma, Conclave itself does not follow in the footsteps of Comma, which only has one function, namely as coworking space. This is the purpose of the study, first to prove that Conclave Wijaya is able to cover and accommodate its function as a place to work and relax, second to study the Conclave Wijaya facility as a container that is able to attract and attract users, and third to see strengths, weaknesses, opportunities and threats on Conclave Wijaya. In order to achieve the objectives of the method used with a qualitative approach can describe the conditions that exist in the Conclave Wijaya and identify aspects that affect the existence of the Conclave Wijaya. The final results achieved indicate the strategy of Conclave Wijaya in its existence that continues to survive amid competition in the coworking space business. Keywords: Analysis; Coworking Space; User; Strategy AbstrakConclave Wijaya sudah berdiri sejak tahun 2013 dan diresmikan ditahun 2014, Conclave Wijaya tidak hanya berfokus pada satu tipe fungsi ruang tetapi selain adanya coworking space disana juga dibangun office space, meeting room, event space, auditorium, dan class room. Identifikasi masalah bermula dari pesatnya perkembangan startup dan usaha mikro kecil dan menengah khususnya di Jakarta. Namun seringnya waktu banyak terobosan baru mengenai konsep dan fungsi dari coworking space yang sesuai kebutuhan konsumen dan tentunya dengan harga terjangkau. Walaupun Conclave Wijaya bekerja sama dengan pihak Comma namun Conclave sendiri tidak mengikuti jejak Comma yang hanya memiliki satu fungsi yakni sebagai coworking space. Hal ini yang menjadi tujuan studi dilakukan, pertama untuk membuktikan Conclave Wijaya mampu mencakup dan mewadahi fungsinya sebagai tempat bekerja dan bersantai, kedua untuk mengkaji fasilitas Conclave Wijaya sebagai  wadah  yang  mampu diminati  dan  menarik pengguna, dan ketiga untuk melihat  kekuatan, kelemahan, peluang dan ancaman pada Conclave Wijaya. Agar tercapainya tujuan metode yang digunakan dengan pendekatan kualitatif dapat mendeskripsikan kondisi yang ada pada Conclave Wijaya serta mengindentifikasi aspek yang mempengaruhi keberadaan Conclave Wijaya. Hasil akhir yang dicapai menunjukkan strategi Conclave Wijaya dalam eksistensinya yang terus bertahan ditengah persaingan bisnis coworking space.